1999
DOI: 10.1002/hep.510290516
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rat Hepatocyte Proliferation by Transforming Growth Factor β and Glucagon Is Associated With Inhibition of Erk2 and P70 S6 Kinase

Abstract: Stimulation of hepatocyte proliferation by epidermal growth factor (EGF) and insulin is inhibited by transforming growth factor ␤ (TGF-␤) and by glucagon. It is also suppressed by inhibitors of various protein kinases, including rapamycin, which blocks activation of p70 S6 kinase (p70 S6k ), PD98059, which inhibits the activation of extracellular-regulated kinase (ERK), and SB 203580, an inhibitor of the p38 mitogen-activated protein kinase (p38 MAPK). In this study, we investigated whether the inhibition of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 59 publications
1
27
1
Order By: Relevance
“…A lower phosphorylation of p70S6K could contribute to the decline in the proliferative response of hepatocytes. 44,45 We demonstrated that downregulation of p70S6K expression with siRNA significantly inhibits DNA synthesis. Furthermore, inhibition of ERK2 by siRNA decreased p70S6K phosphorylation, showing that p70S6K was located downstream of ERK2 in hepatocytes.…”
Section: Discussionmentioning
confidence: 92%
“…A lower phosphorylation of p70S6K could contribute to the decline in the proliferative response of hepatocytes. 44,45 We demonstrated that downregulation of p70S6K expression with siRNA significantly inhibits DNA synthesis. Furthermore, inhibition of ERK2 by siRNA decreased p70S6K phosphorylation, showing that p70S6K was located downstream of ERK2 in hepatocytes.…”
Section: Discussionmentioning
confidence: 92%
“…ERK MAP kinase and PKB(Akt) are activated by EGF in a number of cell types. 15,18,37,49 Time course experiments showed that addition of EGF to primary rat hepatocyte cultures caused sustained stimulation of ERK MAP kinase (p44 MAPK and p42 MAPK) 5 minutes to 2 hours after EGF addition ( Fig. 1A and 1B).…”
Section: Egf Stimulates Erk Map Kinase Activation and Pkb(akt) Activamentioning
confidence: 98%
“…TGF-␤ 1 is a potent inducer of apoptosis in hepatocytes and several hepatoma cell lines, as well as in regressing liver in vivo. 3,36 In vitro, TGF-␤ 1 acts as a physiological inhibitor of cellular proliferation, 1,37 and the addition of TGF-␤ 1 to primary hepatocyte cultures results in high levels of apoptosis. [38][39][40][41] In this study, we have investigated the roles of different signaling pathways engaged by EGF and TNF-␣ in the suppression of TGF-␤ 1 -induced apoptosis.…”
mentioning
confidence: 99%
“…Studies using a perfused rat liver preparation show that glucagon stimulates protein degradation, inhibits protein synthesis, and prevents completely the stimulation of protein synthesis induced by elevated levels of perfusate amino acid concentration (6). Studies using rat hepatocytes show that glucagon attenuates the stimulatory effect of epidermal growth factor on phosphorylation of the ribosomal protein (rp) 1 S6 kinase S6K1 (7).…”
mentioning
confidence: 99%